A review on the use of rice husk ash in construction (Research, Society and Development, 2021)
In recent years, the premature loss of the functional and structural characteristics of buildings, as well as considerable environmental impacts due to the cement production process, led to the development and adoption of supplementary materials to the Portland cement composition to increase the service life of structures and reduction of environmental impacts. In this theme, research on the use of rice husk ash (CCA) in mortars and concrete (partially replacing Portland cement) has been growing, thus generating great advantages in the technical and environmental field. In light of this, this paper presents a review of the use of CCA agro-industrial waste in civil construction. The research was developed from a systematic bibliographic review on the subject, passing through a general approach, presenting the origin, statistical data, applications and technological characteristics on the subject.